220k views
5 votes
Solve the equation.

3(2w−7)=3

2 Answers

3 votes

AnswerAnswerAnswerAnswerAnswerAnswerAnswer

:) ·g o o d l u c k ·

Solve the equation. 3(2w−7)=3-example-1
User Superfav
by
5.1k points
0 votes

Answer:Simplifying

3(2w + -7) = 3

Reorder the terms:

3(-7 + 2w) = 3

(-7 * 3 + 2w * 3) = 3

(-21 + 6w) = 3

Solving

-21 + 6w = 3

Solving for variable 'w'.

Move all terms containing w to the left, all other terms to the right.

Add '21' to each side of the equation.

-21 + 21 + 6w = 3 + 21

Combine like terms: -21 + 21 = 0

0 + 6w = 3 + 21

6w = 3 + 21

Combine like terms: 3 + 21 = 24

6w = 24

Divide each side by '6'.

w = 4

Simplifying

w = 4

Explanation:

User SolveMe
by
4.4k points